Efektivitas Mekanisme dan Prosedur Pembangunan Wilayah Terpadu sebagai Penghubung Rencana Tata Ruang dan Rencana Pembangunan Kota Surakarta - Yustinus Rimas Pramundarto; Samsul Ma'rif (Jurusan Perencanaan Wilayah dan Kota, 2017)
National Development Planning System and Spatial Planning System are two types of planning system prevailing in Indonesia. The planning system essentially has a plan that is aspasial and spatial. Integration between the Development Plan and Spatial Plan for the challenges ahead in the framework of integrity of the effectiveness and efficiency of government administration. One was conducted by the Ministry of the Interior to make a guide that aims to bridge the two domains of the planning system through Pembangunan Wilayah Terpadu (Integrated Regional Development) which is regulated by the Regulation of the Minister of Interior of the Republic of Indonesia Number 72 Year 2013. The main focus in this study aims to assess how effective the mechanisms and procedures Integrated Regional Development Surakarta as an instrument that connects the Development Plan and Spatial Plan using qualitative methods in studying these objectives. Secondary data were obtained from Surakarta City Government planning documents such as RPJMD, RKP, RTRW, RDTR, and PWT. Efforts to bridge between SPPN with SPR needs to be done in order to create the integration of governance in order to realize the sustainable development of Surakarta.